التحليل اللغوي في تفسير ابن عاشور : دراسة منهجية وتحليلية لنماذج من سورتي البقرة وآل عمران - سبوعي، صالح (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This study analyses linguistic views of one of the scholars of Ummah, Muhammad al- Tahir Bin ‘Ashur, through his great work in exegesis of Qur'an (Tafsir al-Tahrir wa al-Tanwir) to deduce principles that could help in understanding the linguistic texts and find out their goals and purposes. The research focuses on linguistic analysis of Ibn ‘Ashur in his exegesis, and establishes that his linguistic views can be adopted as an integrated methodology to analyze different type of texts. This study presents the importance of purposes of Shari‘ah, its role in the understanding of texts, and the true essence of their themes. The research revises some analytical methods used in analyzing Shari‘ah texts, and demonstrates the importance of knowledge of the Arabic language and norms of its use according to Arab culture in understanding Shari‘ah and deduct rules from it. The analytical examples – both purposive and thematicpresented by the researcher in this study stand as a sound proof of possibility of transforming ideas of Muslim scholars into theoretical methods which can be turned into practice. The work comes in seven chapters which discuss the linguistic analysis in exegesis of Qur'ān, the linguistic analysis of Ibn ‘Ashur and its principles, linguistic issues advanced by Ibn ‘Ashur which help to understand the theoretical and intellectual bases of his linguistic analysis, and samples of analysis of selected verses from Qur'anic chapters of al-Baqarah and Āl 'Imran based on principles derived from Ibn ‘Ashur's analysis. The study concludes that Ibn ‘Ashur’s linguistic analysis transcends its time and it is comparable in some respects to the contemporary linguistic ideas. Moreover, it is found that Ibn ‘Ashur’s linguistic thought is very much related to his understanding of Shari‘ah objectives. Lastly, the study shows that it is possible to transform Ibn ‘Ashur's linguistic analyses into a linguistic analytical methodology which could help in the understanding of purposes of texts. Such analysis may start with attempts to understand the text to conclude the objectives, as it may start from thematic analysis of the text to conclude with its purpose.